Juiz de garantias: fundamentos epistemológicos e das ciências cognitivas para a promoção da imparcialidade no processo penal - Oliveira, Hélio Roberto Cabral de (2023)
The Federal Law 13964/2019, popularly known as the “Pacote Anticrime”, inaugurated the guarantee judge in the Brazilian legal system. This innovation, in summary, is a functional division of the criminal jurisdictional competence of the first instance in the figure of two distinct judges: the first, the guarantees judge, is responsible for controlling the legality of the investigation and for guaranteeing the rights of the investigated person, whose competence ends with the decision to confirm receipt or not of the criminal complaint; the second, the judge of the case, will preside over the process without access to the investigation records, being responsible for instructing the case and will judge the merits of the criminal action with cognitive originality. Such procedural reform brought great debates in the legal environment. On the one hand, its defenders understand that the new procedural model is important to improve the Brazilian criminal procedure, bringing it more democracy by providing greater judicial impartiality, by promoting the presumption of innocence, the contradictory and defense to a greater degree. On the other hand, its critics understand that the aforementioned functional division would be inadequate to the budgetary and administrative reality of the Brazilian courts, as well as not only not promoting greater judicial impartiality but also harming the national criminal process. This discussion culminated in the preliminary decision of the Minister of the Federal Supreme Court Luiz Fux who, as rapporteur of ADIs 6298, 6299, 6300 and 6305, ad referendum of the plenary, even before the entry into force of Federal Law 13964/19, suspended the effectiveness of various legal provisions of the said law to prevent the beginning of the effectiveness of the institute of the guarantee judge. However, it appears that most defenses and criticisms are made from a merely normative perspective, ending up being limited to an extremely formal, intuitive and speculative approach. Considering that an exclusively analytical examination of the guarantee judge is insufficient, the present work will aim at its interdisciplinary approach, using, for this purpose, the theoretical frameworks of Legal Epistemology and Cognitive Sciences. Thus, the aim is to observe both how the new procedural model can contribute to a more accurate judicial investigation of the facts, bringing greater reliability to the criminal process, as well as how it can avoid a potentially biased attitude of judges, whether in favor of the prosecution or in favor of the defense. Bearing in mind that the decision of the plenary of the Federal Supreme Court is still pending, the study of the guarantee judge in the academic field proves to be essential to collaborate with the discussion about its constitutional legitimacy. The methodology used in this research was of a qualitative nature, seeking to understand and interpret the subject based on the critical analysis of theoretical and scientific texts. For that, bibliographical research was used, through the analysis of books, articles and empirical studies, as well as Brazilian and foreign documents, and national and international legislation and jurisprudence.